EU competition law and the information and communication technology network industries : economic versus legal concepts in pursuit of (consumer) welfare - Fatur, Andrej (Hart studies in competition law., 2012)
Competition policies have long been based on a scholarly tradition focused on static models and static analysis of industrial organisation. However, recent developments in industrial organisation literature have led to significant advances, moving beyond traditional static models and a preoccupation with price competition, to consider the organisation of industries in a dynamic context. This is especially important in the field of information and communication technology (ICT) network industries where competition centres on network effects, innovation and intellectual property rights, and where the key driver of consumer benefit is technological progress. Consequently, when an antitrust intervention is contemplated, a number of considerations that arise out of the specific nature of the ICT sector have to be taken into account to ensure improved consumer welfare. This book considers the adequacy of existing EU competition policy in the area of the ICT industries in the light of the findings of modern economic theory. Particular attention is given to the implications of these dynamic markets for the competitive assessment and treatment of the most common competitive harms in this area, such as non-price predatory practices, tying and bundling, co-operative standard setting, platform joint ventures and co-operative R & D.